1998
DOI: 10.1023/a:1006957415346
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A retrospective study of 325 cases of chromoblastomycosis diagnosed in the last 55 years in the Amazon region was carried out by the main Mycology services of the state of Pará, Brazil (Department of Tropical Pathology--UFPA and Mycology Department of the Evandro Chagas Institute/FNS). The data obtained showed that: (a) the main age group affected by the diseases range from 41 to 70 years-old, (b) 86.1% of the patients were agricultural-workers, (c) 93.2% of them were males and (d) 80.7% showed lesions on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(31 citation statements)
references
References 13 publications
3
27
0
1
Order By: Relevance
“…The sex distribution in a case series reported in the southern region of Brazil showed that disease was prevalent in males (4:1) (126). In two other studies involving 390 cases in the same region, the sex ratio distribution was much higher for males (17:1) (123,124). The difference related to sex distribution in patients with CBM may be related to hormonal protection, as observed for paracoccidioidomycosis patients (150).…”
Section: Demographics and Risk Factorsmentioning
confidence: 74%
See 3 more Smart Citations
“…The sex distribution in a case series reported in the southern region of Brazil showed that disease was prevalent in males (4:1) (126). In two other studies involving 390 cases in the same region, the sex ratio distribution was much higher for males (17:1) (123,124). The difference related to sex distribution in patients with CBM may be related to hormonal protection, as observed for paracoccidioidomycosis patients (150).…”
Section: Demographics and Risk Factorsmentioning
confidence: 74%
“…After Brazil, Venezuela and Colombia account for most cases of CBM. Within Brazil, CBM is endemic in many geographical areas, especially in the northern regions, where 872 cases were retrospectively reported during the last decades (3,79,123,124). Although 332 cases were reported from other provinces, a significant decrease in the number of new CBM cases has been observed, especially in the southern regions of this country (125,126).…”
Section: Chromoblastomycosis In the Americasmentioning
confidence: 99%
See 2 more Smart Citations
“…The state of Maranhão in northeast Brazil is a region of chromoblastomycosis hyperendemicity. Fonsecaea pedrosoi is classically assumed to be responsible for almost 99% of the clinical cases (21,22). However, since Fonsecaea agents of the disease are morphologically indistinguishable (2,5,23) and specimens from cases have mostly not been cultured, it is possible that other agents have a higher prevalence than currently thought.…”
mentioning
confidence: 99%